2022
DOI: 10.21203/rs.3.rs-839497/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Open defecation: risk factors for adverse outcomes in Indonesia

Abstract: The increasing number of Indonesian population has caused serious issue of open defecation. Indonesia ranks the second large of open defecation prevalence in the world, after India. Human’s excrement was disposed in trench, drain, terrace, grassland, backwoods, forest, river, lake or other open spaces, thus, contaminates the water system. Open defecation can lead to the increasing risk of transmission of water-boene diseases of child morbidity in Indonesia. This study aimed at exploring different socio-economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…These results align with earlier studies carried out in Ghana 49.5% [24], and Benin 53.9% . However, the open defecation rates were greater than those recorded in Kenya 23.5% [32], Senegal 12.4% , Nigeria 24.5% [30] and Indonesia 28.5% [33], but lower than those observed in Niger 72.7% and Chad 70.6%, respectively . The variation in open defecation rates could be attributed to the differences in implementation frameworks, socioeconomic statuses, and study design approaches [34].…”
Section: Discussionmentioning
confidence: 56%
“…These results align with earlier studies carried out in Ghana 49.5% [24], and Benin 53.9% . However, the open defecation rates were greater than those recorded in Kenya 23.5% [32], Senegal 12.4% , Nigeria 24.5% [30] and Indonesia 28.5% [33], but lower than those observed in Niger 72.7% and Chad 70.6%, respectively . The variation in open defecation rates could be attributed to the differences in implementation frameworks, socioeconomic statuses, and study design approaches [34].…”
Section: Discussionmentioning
confidence: 56%
“…Indonesia has the second most prevalent open defecation after India. 23 As we mentioned, in Balangan, the community has a habit of defecating in the river, and children go to school wearing flip-flops. A study in Northwest Ethiopia revealed that open defecation practices are associated with STH prevalence.…”
Section: Discussionmentioning
confidence: 99%